Sequential Extended S-Metric Spaces and Relevant Fixed Point Results with Application to Nonlinear Integral Equations - Abdollah Karami; Shaban Sedghi; Vahid Parvaneh (Advances in Mathematical Physics)
In this paper, the notion of sequential ςp-metric spaces has been introduced as a generalization of usual S-metric spaces, Sb-metric spaces, SJS metric spaces, and specially of Sp-metric spaces. In view of this notion, we prove some fixed point theorems for some classes of ςp-rational Geraghty JS-contractions over such spaces. A supporting example and an application have been given in order to examine the validity of the obtained results.